Best Practices in Interconnecting Sharia Arbitration Norms: A Comparative Analysis of Indonesia and Europe - Suadi, Amran; Affandi, Muchammad Taufiq (Indonesian Journal of Islamic Economic Law, 2024)
This paper explores the intricate process of interconnecting Sharia law with the legal systems of Europe, with a focus on the theoretical perspectives presented by Robert Alexy and H.L.A. Hart. It delves into the complexity and challenges associated with this integration and identifies key points of contention and opportunities. Notable challenges include overcoming the negative perceptions of Sharia law within Western legal circles, recognizing the diverse interpretations of Sharia, and harmonizing capitalist and Shariacompliant economic principles. The paper emphasizes the significance of interconnecting Sharia law with European legal systems, particularly within the realm of economic law, where concepts of justice, ethics, and Sharia's intricate provisions come into play. Using the theoretical frameworks of Alexy and Hart, the paper operationalizes the variables of "cause" and "effect" through comparative analysis to facilitate an effective and fair interconnection. It concludes by highlighting the importance of embracing an approach that balances the relevant aspects while minimizing legal uncertainties. In achieving this balance, the paper suggests strategies such as defining clear Sharia arbitration rules and ensuring the coexistence of Islamic banking practices with public interests. The evolving interaction between the two legal systems driven by the growing relevance of Islamic law necessitates a diverse legal landscape with various implications for Europe's everevolving legal framework.